5 gears : how to be present and productive when theres never enough time - Kubicek, Jeremie; Cockram, Steve (Hoboken : Wiley, 2015)
"Why do most people stay disconnected? And, why do some connect brilliantly? Get in Gear is meant to unleash people, to allow them to connect deeply and genuinely. It is meant to overwhelm them with piercing insights coupled with practical applications. The goal is to take a complex issue and make it simple enough for anyone to be able to change their behavior. Get in Gear positively affects the relational dynamics of those around us is through the use of powerful metaphor, relevant language, and actionable tools via 5 Gears. Everyone who reads it will come away speaking a new language, one that helps them connect deeper and more genuinely with anyone in any setting. And with these deeper connections comes deeper relationships and greater influence. Practical goodness and needed insight will change your world - at least in your family or team or just maybe within yourself! The 5 Gears: First gear represents full recharge, while second gear represents recharging or connecting with family or friends without the involvement of work. Third gear is our social gear, while fourth gear is our work gear that allows us to work hard while also multi-tasking. Fifth Gear is our full task mode that allows us to "get in the zone" without interruption. Each gear has its own purpose and place. Once you learn to use the gears consistently with those in your life, you will notice the common language that begins to form, enabling objectivity to characterize your conversation instead of the subjective judgment or condescension that becomes pervasive when each person is speaking a different "language.""--
Front matter -- Introduction -- Connectivity. Driving too fast -- Reality check -- 5 gears for practical connection. Getting in gear -- 5th gear: in the zone -- 4th gear: leading in a task world -- 3rd gear: why being social matters -- 2nd gear: connecting deeply -- 1st gear: learning to recharge -- Reverse: being responsive in a resistant world -- Ranking your gear order -- Living and leading connected. Master your settings: right time, right place -- Shifting well: learning how to transition -- Intentional versus accidental -- Making the u-turn: challenge and plan -- What is your story? -- Transformational leadership resources -- About GiANT Worldwide -- Acknowledgments -- Index.
Includes index.
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Leadership; Interpersonal relations; Self-actualization (Psychology); SELF-HELP -- General; SELF-HELP -- Personal Growth -- General; BUSINESS & ECONOMICS -- Leadership; Interpersonal relations; Leadership; Self-actualization (Psychology); Electronic books; Electronic books